The Impact of Sustainable Development on Community Welfare and Quality of Life: An Exploratory Study of the Views of a Sample of Students at the College of Administration and Economics - Mosul University (Sebha University Conference Proceedings, 2024)
The research explores the impact of sustainable development dimensions (economic, environmental, and social) on achieving community well-being and quality of life. Based on the main research question, which addresses the research problem: "To what extent do the dimensions of sustainable development contribute to the well-being of the community and quality of life among students at the College of Administration and Economics at the University of Mosul?" In response to this question, a questionnaire was distributed to a random sample of (292) students from the mentioned college. Three hypotheses were formulated to determine the nature of the correlation and impact between the main research variables. According to these hypotheses, a hypothetical model for the research was constructed. By using a correlational methodology for data collection and analysis with statistical methods (correlation coefficient, regression, mean, standard deviation) through the (SPSS V-26) program, the results showed a positive and significant correlation between sustainable development and community well-being and quality of life, at both the aggregate and partial levels. Additionally, the college council members effectively apply the dimensions of sustainable development, as the research indicates a strong positive response from students toward sustainable development initiatives. This highlights the importance of incorporating sustainable development concepts into educational and awareness programs for youth. The economic dimension appeared to be the most important and influential on the dependent variable. Based on the current results, increasing efforts to promote sustainable development in the community, particularly among youth and students, is recommended to enhance their well-being and quality of life and contribute to building a more sustainable society in the long term.